Nurses-Led Municipal Leadership and Governance Program: Experiences of Local Chief Executives in Central Visayas, Philippines - Palompon, Daisy R.; Naranjo, Michele A.; Abalos, Evalyn; Omus, Nelner; Flores, Philip Jerome A. (Belitung Nursing Journal, 2024)
Background: The strategic response of nurses in addressing health inequities in marginal sectors led to the conduct of a health leadership governance training program for local chief executives. Objective: This study aimed to explore and provide a description of the experiences of local chief executives (LCEs) or mayors who participated in the nurse-initiated health training named Municipal Leadership and Governance Program (MLGP). Methods: A qualitative descriptive design was used through key informant interviews of fifteen mayors or local chief executives (LCE) in the provinces of Bohol and Negros Oriental, Philippines. Data were collected from 16 to 20 November 2022 and analyzed using a thematic approach. Results: The findings generated six themes: a) Leadership capacitation promoting transformative experience, b) Pandemic and program-induced limitations in the training implementation, c) Personal leadership motivation, d) Experiential learning promoting learning as applied in real-world situations, e) Celebrating leadership transformation, and f) 3R’s of MLGP: revisit, review, recommend. Conclusion: The realizations of the training participants provided valuable implications for the quality of training offered by nurse leaders who advocated the MLGP implementation. It served as a proactive and responsive approach to the health leadership capacitation of mayors. It guided them in their personal realizations that inspired them to apply what they had learned and enabled them to effect experiences of personal to institutional transformation.